2018
DOI: 10.1371/journal.pone.0198558
|View full text |Cite
|
Sign up to set email alerts
|

Phytoliths as an indicator of early modern humans plant gathering strategies, fire fuel and site occupation intensity during the Middle Stone Age at Pinnacle Point 5-6 (south coast, South Africa)

Abstract: The study of plant remains in archaeological sites, along with a better understanding of the use of plants by prehistoric populations, can help us shed light on changes in survival strategies of hunter-gatherers and consequent impacts on modern human cognition, social organization, and technology. The archaeological locality of Pinnacle Point (Mossel Bay, South Africa) includes a series of coastal caves, rock-shelters, and open-air sites with human occupations spanning the Acheulian through Middle Stone Age (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 104 publications
2
36
0
Order By: Relevance
“…However, the simultaneous presence of biogenic aragonite from shells, which is a common component of the archaeological record at many sites across the globe, requires a spectroscopic approach able to distinguish between the two. This becomes especially apparent in the case of combustion features where aragonite may be present as a byproduct of high-temperature burning of fuel and as shell fragments embedded in the sedimentary matrix [51,52]. The same applies to aragonitic shells embedded in lime mortars [53].…”
Section: Aragonite In Heat-altered Sedimentsmentioning
confidence: 98%
“…However, the simultaneous presence of biogenic aragonite from shells, which is a common component of the archaeological record at many sites across the globe, requires a spectroscopic approach able to distinguish between the two. This becomes especially apparent in the case of combustion features where aragonite may be present as a byproduct of high-temperature burning of fuel and as shell fragments embedded in the sedimentary matrix [51,52]. The same applies to aragonitic shells embedded in lime mortars [53].…”
Section: Aragonite In Heat-altered Sedimentsmentioning
confidence: 98%
“…(2) the percentage of fragile morphologies (Esteban et al 2018, and references therein); (3) the diversity of the phytolith assemblage (number of morphotypes identified; Madella and Lancelotti 2012); and (4) the percentage of broken grass silica short cell phytoliths (GSSCPs) bilobate for each unit. This method measures the strength and direction of the association between two ranked variables (phytolith concentration and the taphonomic indicators).…”
Section: Taphonomical Analysismentioning
confidence: 99%
“…Weiner, Goldberg, and Bar‐Yosef (2002) tracked with FTIR the three‐dimensional distribution of aragonite within prehistoric sediments at Hayonim Cave, Israel, to exclude bone dissolution in places where aragonite was preserved but bones were not found. A similar approach was used at other prehistoric sites such as Kebara Cave, also located in Israel (Weiner et al, 2007), Grotte XVI in France (Karkanas, Rigaud, Simek, Albert, & Weiner, 2002), Pinnacle Point 5‐6 in South Africa (Esteban et al, 2018), and at Iron Age Tell es‐Safi/Gath, Israel (Namdar et al, 2011). Aldeias, Goldberg, Dibble, and El‐Hajraoui (2014) characterized the degree of preservation of biogenic aragonite at Contrebandiers Cave (Morocco) using micromorphology thin sections.…”
Section: Archaeological Significancementioning
confidence: 99%
“…They showed that biogenic aragonite from G. insubrica , one of the most common bivalves found at archaeological sites in Israel (e.g., Sivan et al, 2006), has a grinding curve markedly different from the curve of pyrogenic aragonite (Figure 3). Therefore, it is possible to assess whether aragonite found within combustion features is of biogenic or pyrogenic origin (e.g., Albert et al, 2008, table 2; Esteban et al, 2018). This method should be calibrated based on the type of biogenic aragonite available at the site, since different organisms mineralize aragonite crystals with various degrees of atomic order (Suzuki et al, 2011).…”
Section: Archaeological Significancementioning
confidence: 99%